Case Report: Paraneoplastic Hashimoto's Encephalopathy Associated With Lymphomatosis Cerebri With Periodic Synchronous Discharges Resembling Creutzfeldt–Jakob Disease - Amano, Ryota; Tsukada, Setsuro; Kosuge, Shota; Yano, Satoshi; Ono, Kenjiro; Yoneda, Makoto; Taki, Katsumi (Frontiers in Neurology, 2021)
Hashimoto’s encephalopathy (HE) is an autoimmune encephalopathy that presents with various clinical symptoms, including cognitive deterioration, convulsive seizures, and personality changes. HE is associated with thyroid autoimmunity; however, few cases have been reported to be developed as the paraneoplastic syndrome. Herein, we report the case of a 73-year-old woman with the onset of rapidly progressive dementia. Brain magnetic resonance imaging showed diffuse T2 hyperintensity areas involving the bilateral cerebral white matter, right midbrain tegmental area, left cerebral peduncle, and right middle cerebellar peduncle without clear diffusion hyperintensities and gadolinium enhancement. Her neurological symptoms worsened rapidly, and she presented with the apallic syndrome. Electroencephalogram showed periodic synchronous discharge, suggestive of Creutzfeldt-Jakob disease. However, a brain biopsy revealed infiltration of atypical lymphoid cells expressing CD20, and the anti-NH2 terminal of the α-enolase antibody was detected, diagnosing the complication with lymphomatosis cerebri and HE. High-dose intravenous methylprednisolone therapy and oral prednisolone with whole cranial irradiation enabled her to have simple conversations and consume food orally; however, severe cognitive impairment persisted. Although HE is a rare complication of malignant lymphoma, clinicians should be aware that HE could be strongly suspected if clinical symptoms worsen in the absence of imaging changes.